A sociological study of changes of women life styles in cyberspace interactions - Galini, Marzieh; Sedaghati Fard, Mojtaba; Parnian, Shideh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This aim of this study was sociological investigation of lifestyle changes of women in Garmsar city in cyberspace interactions. Methods: A survey and statistical community of women aged 19 to 59 years in Garmsar city was conducted by random sampling method on 160 women of this city. The validity of the measurement scale made by the researcher was checked and confirmed by related experts, and the reliability of the questionnaire was calculated using Cronbach’s alpha method and its coefficient was 0.75 in the questionnaire. The data were evaluated using Pearson correlation coefficient, U-Mann-Whitney test and Spss software. Results: between lifestyle indicators, attention to the body (r=0.42, P=0.027), leisure patterns and spending time (r=0.34, P=0.031), nutrition (r=0.23, P=0.048), social communication (r=0.38, P=0.039), marriage or cohabitation style (r=0.44, P=0.022), and sports (r=0.21, P=0.031) has a relationship with the activity in the virtual space, so that the amount of presence in the virtual space has increased the amount of tendency towards the aforementioned indicators and the non-traditional (modern) lifestyle among them. Conclusion: There were changes and differences in the lives of the investigated women, and the conducted investigations show a significant situation in this regard. Therefore, the activity and interaction in the virtual space has been able to significantly change the lifestyle of the studied women. In fact, these changes show the significant impact that presence in virtual space can have on women’s lifestyle in terms of sociology. Based on this, it was suggested that the policy makers and relevant officials regarding cyberspace should direct their attention to changing the security view, to a cultural view for better social policies and to a more positive and effective direction.